Bifurcation of solutions of a linear Fredholm boundary-value problem - Chuiko, S. M. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
We establish constructive conditions for the appearance of solutions of a linear Fredholm boundary-value problem for a system of ordinary differential equations in the critical case and propose an iterative procedure for finding these solutions. The range of values of a small parameter for which the indicated iterative procedure is convergent is estimated.